Size of cervical lesion in locally advanced carcinoma cervix and response to neoadjuvant chemotherapy - Ahirwar, Neetu (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2019)
Background: Recently neoadjuvant chemotherapy has started being considered for advanced stage of carcinoma cervix. Drug delivery to pelvic tumour is optimal with neoadjuvant chemotherapy since tumour vascular supply has not been damaged by any previous pelvic interference. Tumor size and parametrial involvement have been reported to be important predictor of NACT response. Objective of this study was to find out association between size of cervical lesion in locally advanced carcinoma cervix and response to neoadjuvant chemotherapy. Methods: The present prospective cohort study was carried out in the Department of Obstetrics and Gynaecology with the collaboration of Department of Radiotherapy, Chhatrapati Shahuji Maharaj Medical University Lucknow for a period of 1-year august 2010 to august 2011. 26 patients with histologically proven locally advanced carcinoma cervix were studied. In all cases Cisplatin 75 mg/m2 and paclitaxel 135 mg/m2 on day one was given at 14 days interval up to maximum of three courses. Evaluation of operability status was done two weeks after second course of chemotherapy. Those found operable were taken up for radical hysterectomy and rest were given 3rd course of chemotherapy. After two weeks of 3rd course again operability assessment was done and patient was taken up either for surgery or radiotherapy. Results: It was observed that out of 14 patients who had tumour size <4 cm, 9 (64.2%) responded completely (CR), 2 (14.2%) responded partially and 3 (21.4%) responded as SD while in 12 patients with tumour size >4 cm, 4 (33.3%) responded completely (CR) and rest 8 (66.6%) response was partial (PR). Conclusions: Response to chemotherapy was modified by pre-treatment volume of the tumour.